VOLUNTARY COUNSELLING AND TESTING (VCT) SERVICES ON HIV/AIDS IN PRIVATE HOSPITAL OF YOGYAKARTA - Suci Musvita Ayu; Desy Riski Andriyanti (Epidemiology and Society Health Review (ESHR), 2020)
Background: Data Yogyakarta AIDS Commission in 2016 stated the total number of people living with HIV/AIDS was 4,648 cases consisting of 3,334 HIV cases and 1,314 AIDS cases. Based on the data of PKU Muhammadiyah Hospital, Yogyakarta, in October 2016 to October 2017, there were 35 patients with HIV / AIDS. Regulations carried out for any action in the hospital must be following standard operating procedures (SOP), including program counseling and testing of HIV/AIDS or Voluntary Counselling and Testing (VCT). This program is the gateway for the community to gain access to all HIV/AIDS services. This study aimed to explore the implementation of VCT services on HIV/AIDS at PKU Muhammadiyah Hospital in Yogyakarta.Methods: Descriptive qualitative using an observational approach was used in this study to describe the implementation of Voluntary Counselling and Testing (VCT) on HIV/AIDS. Â As many as ten informants were interviewed, namely: 1 head of VCT services in PKU Muhammadiyah Yogyakarta, 3 VCT counselors, 1 laboratory staff and 5 clients. They were selected using purposive sampling refers to inclusion criteria. Â Results: Implementation of pre-test counseling, testing, and post-test had been good. Improper service was identified in the number of counselors and waiting time for the VCT test results.Conclusions: Implementation of VCT at PKU Muhammadiyah Yogyakarta is running well and follow the SOPs.Â